The structure of importin α and the nuclear localization peptide of ChREBP, and small compound inhibitors of ChREBP–importin α interactions. Issue 17 (10th September 2020) - Jung, Hunmin; Takeshima, Tomomi; Nakagawa, Tsutomu; MacMillan, Karen S.; Wynn, R. Max; Wang, Hanzhi; Sakiyama, Haruhiko; Wei, Shuguang; Li, Yang; Bruick, Richard K.; Posner, Bruce A.; De Brabander, Jef K.; et al.
Abstract : The carbohydrate response element binding protein (ChREBP) is a glucose-responsive transcription factor that plays a critical role in glucose-mediated induction of genes involved in hepatic glycolysis and lipogenesis. In response to fluctuating blood glucose levels ChREBP activity is regulated mainly by nucleocytoplasmic shuttling of ChREBP. Under high glucose ChREBP binds to importin α and importin β and translocates into the nucleus to initiate transcription. We have previously shown that the nuclear localization signal site (NLS) for ChREBP is bipartite with the NLS extending from Arg158 to Lys190. Here, we report the 2.5 Å crystal structure of the ChREBP-NLS peptide bound to importin α. The structure revealed that the NLS binding is monopartite, with the amino acid residues K 171 RRI 174 from the ChREBP-NLS interacting with ARM2–ARM5 on importin α. We discovered that importin α also binds to the primary binding site of the 14-3-3 proteins with high affinity, which suggests that both importin α and 14-3-3 are each competing with the other for this broad-binding region (residues 117–196) on ChREBP. We screened a small compound library and identified two novel compounds that inhibit the ChREBP-NLS/importin α interaction, nuclear localization, and transcription activities of ChREBP. These candidate molecules support developing inhibitors of ChREBP that may be useful in treatment of obesity and the associated diseases.